Effects of Different Ratios of Fly Ash and River Sand on Mechanical Properties of Cemented Paste Backfill Materials - Jiang Li; Shenggen Cao; Yang Liu; Chiyuan Che; Changzheng Zhao; Shuyu Du; Kaifei Wang; Ruiting Ma (Advances in Civil Engineering)
The mechanical properties of cemented paste backfill (CPB) are crucial for stope safety. Some mining areas in the Yellow River basin face a shortage of coal gangue, and these areas have abundant river sand (RS) resources. The use of RS as a fine aggregate can optimize the particle gradation of the material and improve the strength of the material. The effects of different fly ash (FA) and RS ratios on uniaxial compressive strength (UCS), elastic modulus, and microstructure of CPB were studied using uniaxial compression test and scanning electron microscopy. The results showed that with increasing FA content, UCS gradually increased at 7 and 14 days of CPB. However, at 28 days, the UCS of CPB first increased and then decreased. When the FA content was 40%, UCS at 28 days of backfill material reached its highest value of 14.76 MPa. The elastic modulus decreased as FA content increased and reached its maximum value of 1.54 GPa when FA content was 40%. FA optimized particle composition, promoted hydration reaction, and improved CPB strength; however, when FA content was more than 40%, it hindered cement hydration, thus deteriorating UCS. Based on Weibull distribution and prepeak correction factor, a damage constitutive model was established to describe the stress–strain process of CPB under load. The results of this research will provide a theoretical and experimental basis for CPB engineering design.